Expert consensus on dental caries management - Cheng, Lei; Zhang, Lu; Yue, Lin; Ling, Junqi; Fan, Mingwen; Yang, Deqin; Huang, Zhengwei; Niu, Yumei; Liu, Jianguo; Zhao, Jin; Li, Yanhong; Guo, Bin; et al. (International journal of oral science, 2022)
Dental Caries is a kind of chronic oral disease that greatly threaten human being’s health. Though dentists and researchers struggled for decades to combat this oral disease, the incidence and prevalence of dental caries remain quite high. Therefore, improving the disease management is a key issue for the whole population and life cycle management of dental caries. So clinical difficulty assessment system of caries prevention and management is established based on dental caries diagnosis and classification. Dentists should perform oral examination and establish dental records at each visit. When treatment plan is made on the base of caries risk assessment and carious lesion activity, we need to work out patient‑centered and personalized treatment planning to regain oral microecological balance, to control caries progression and to restore the structure and function of the carious teeth. And the follow-up visits are made based on personalized caries management. This expert consensus mainly discusses caries risk assessment, caries treatment difficulty assessment and dental caries treatment plan, which are the most important parts of caries management in the whole life cycle.